The social function of the logic of the absurd in comedy: approximations between Bergson’s “Laughter” and Jarry’s Ubu Roi - Carvalho, Márcio Marques de (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
The parallels between the arguments in Bergson’s “Laughter” and the aesthetic resources (presented four years earlier in Ubu Roi) by his former student Jarry are remarkable. This study analyzes these similarities to point out the social function of the comic. It looks at aesthetic resources such as artificiality, impersonality, generality, exaggeration, repetition, fixation, and mechanization to list certain social aspects that require correction of their existential weight, thus enabling indirect moral reflection. The influences of children’s games, such as puppets, spring puppets and snowballs, on the way events are presented in comic dramaturgy are also analyzed to encourage the acknowledgement of inadequacies in behavior and character in a light and palatable way. The central argument states that laughter has a social, critical and corrective function that is triggered by an absurd intellectual mode of operation separated from reason and close to imagination and dreaming, which proves to be fundamental for the elaboration of important issues society strives to deny.